2021
DOI: 10.1093/cid/ciab321
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Severe Acute Respiratory Syndrome Coronavirus 2 Transmission Among Attendees at a Large Motorcycle Rally and their Contacts, 30 US Jurisdictions, August–September, 2020

Abstract: The 2020 Sturgis Motorcycle rally resulted in widespread transmission of SARS-CoV-2 across the United States. At least 649 COVID-19 cases were identified, including secondary and tertiary spread to close contacts. To limit transmission, persons attending events should wear masks and practice physical distancing. Persons with a known exposure should quarantine and obtain COVID-19 testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…An analytical model of SARS-CoV-2 transmission argues that more than half of all transmission is from asymptomatic carriers, including both individuals who are presymptomatic and individuals with true asymptomatic infections who never develop symptoms 23 . During a period when those with known PCR-positive symptomatic infections have tended to self-isolate, ‘superspreader’ clusters after large events (such as the Sturgis Motorcycle Rally (South Dakota, USA) attended by half a million bikers in August 2020) 30 were attributed to spread from individuals with presymptomatic and/or asymptomatic infections. A recent study estimated the infectiousness of individuals who were presymptomatic, asymptomatic or mildly symptomatic 31 .…”
Section: Transmission By Asymptomatic Individualsmentioning
confidence: 99%
“…An analytical model of SARS-CoV-2 transmission argues that more than half of all transmission is from asymptomatic carriers, including both individuals who are presymptomatic and individuals with true asymptomatic infections who never develop symptoms 23 . During a period when those with known PCR-positive symptomatic infections have tended to self-isolate, ‘superspreader’ clusters after large events (such as the Sturgis Motorcycle Rally (South Dakota, USA) attended by half a million bikers in August 2020) 30 were attributed to spread from individuals with presymptomatic and/or asymptomatic infections. A recent study estimated the infectiousness of individuals who were presymptomatic, asymptomatic or mildly symptomatic 31 .…”
Section: Transmission By Asymptomatic Individualsmentioning
confidence: 99%
“…Masks and social distancing were recommended, but not required, and were subsequently ignored by many attendees. Subsequent epidemiologic analysis revealed that at least 649 COVID-19 cases and one death in 10 US states could be connected to the rally, although the actual figures were probably higher, since many attendees refused to cooperate with health authorities [ 38 ]. Cell phone data showed that 61% of US counties had been visited by a Sturgis Rally attendee, creating a travel hub comparable to a major US city, with analyses estimating that the rally generated public health costs of approximately $12.2 billion [ 39 ], although the study's methodology have been questioned.…”
Section: Government Regulations Individual Freedoms and Public Trustmentioning
confidence: 99%
“…These findings underscore the risk for COVID-19 outbreaks at camps and large events where prevention strategies are not implemented and highlight the importance of implementing such strategies to reduce transmission of SARS-CoV-2 in these settings (8). Promoting vaccination, implementing and encouraging compliance with prompt quarantine and isolation measures for exposed and infected persons, staying home when sick, and using nonpharmaceutical interventions including masking, physical distancing, and screening testing in large group settings can help reduce secondary infections in homes and the community and serious complications from COVID-19 (9).…”
Section: What Is Already Known About This Topic?mentioning
confidence: 86%